Answer:
Thus, the two root of the given quadratic equation
is 2 and -3 .
Step-by-step explanation:
Consider, the given Quadratic equation, ![x^2-6=-x](https://tex.z-dn.net/?f=x%5E2-6%3D-x)
This can be written as , ![x^2+x-6=0](https://tex.z-dn.net/?f=x%5E2%2Bx-6%3D0)
We have to solve using quadratic formula,
For a given quadratic equation
we can find roots using,
...........(1)
Where,
is the discriminant.
Here, a = 1 , b = 1 , c = -6
Substitute in (1) , we get,
![x=\frac{-b\pm\sqrt{b^2-4ac}}{2a}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-b%5Cpm%5Csqrt%7Bb%5E2-4ac%7D%7D%7B2a%7D)
![\Rightarrow x=\frac{-(1)\pm\sqrt{(1)^2-4\cdot 1 \cdot (-6)}}{2 \cdot 1}](https://tex.z-dn.net/?f=%5CRightarrow%20x%3D%5Cfrac%7B-%281%29%5Cpm%5Csqrt%7B%281%29%5E2-4%5Ccdot%201%20%5Ccdot%20%28-6%29%7D%7D%7B2%20%5Ccdot%201%7D)
![\Rightarrow x=\frac{-1\pm\sqrt{25}}{2}](https://tex.z-dn.net/?f=%5CRightarrow%20x%3D%5Cfrac%7B-1%5Cpm%5Csqrt%7B25%7D%7D%7B2%7D)
![\Rightarrow x=\frac{-1\pm 5}{2}](https://tex.z-dn.net/?f=%5CRightarrow%20x%3D%5Cfrac%7B-1%5Cpm%205%7D%7B2%7D)
and ![\Rightarrow x_2=\frac{-1-5}{2}](https://tex.z-dn.net/?f=%5CRightarrow%20x_2%3D%5Cfrac%7B-1-5%7D%7B2%7D)
and ![\Rightarrow x_2=\frac{-6}{2}](https://tex.z-dn.net/?f=%5CRightarrow%20x_2%3D%5Cfrac%7B-6%7D%7B2%7D)
and ![\Rightarrow x_2=-3](https://tex.z-dn.net/?f=%5CRightarrow%20x_2%3D-3)
Thus, the two root of the given quadratic equation
is 2 and -3 .